Analisis perhitungan dan pelaporan Pajak Penghasilan Pasal 21 di PT. Celebes Indonesia (Manado Quality Hotel) - Poluan , Verrel Marcel; Kalangi, Lintje; Tangkuman , Steven Josia (Yayasan Widyantara Nawasena Raharja, 2024)
This study aims to determine how the calculation and reporting of tax article 21 on employees of PT Celebes Indonesia based on Law No. 7 Year 2021. This study uses descriptive qualitative research with data collection sourced from documents of the company and result of interviews with respondents. The results of this study indicate PT Celebes Indonesia calculates Income Tax 21 using the latest rates based on Law No. 7 of 2021 with self-assessment system, namely the company is responsible for tax collector Income Tax 21. However, it was found that there was still an error calculation of the determination of PKP, where employees in that month should not be taxed but are subject to tax.